2013
DOI: 10.1089/thy.2013.0063
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Thyroid Tissue in the Adrenal Gland: A Report of Two Cases with Pathogenetic Implications

Abstract: Background: Ectopic thyroid tissue is usually found anywhere along the embryonic descent pathway of the medial thyroid anlage from the tongue to the trachea (Wö lfler area). However, ectopic thyroid tissue in the adrenal gland (ETTAG) is not easy to understand on the basis of thyroid embryology; because it is so rare, the possibility of metastasis should first be considered. Here, we describe two cases of ETTAG with pathogenetic implications and review the associated literature. Patient findings: Two cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 31 publications
0
37
0
3
Order By: Relevance
“…7 Importantly, ETT consists of follicular cells and parafollicular cells have not been identified at sites of ectopic thyroid parenchyma in our case as well as in other reports. 19,23 In conclusion, ETT in the adrenal gland is a rare but well-documented occurrence. It nearly always takes the form of a cystic lesion with features that are distinctive enough to be recognized both macroscopically and histologically.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…7 Importantly, ETT consists of follicular cells and parafollicular cells have not been identified at sites of ectopic thyroid parenchyma in our case as well as in other reports. 19,23 In conclusion, ETT in the adrenal gland is a rare but well-documented occurrence. It nearly always takes the form of a cystic lesion with features that are distinctive enough to be recognized both macroscopically and histologically.…”
Section: Discussionmentioning
confidence: 84%
“…The majority of patients have no endocrine abnormalities, but in 2 there was hyperaldosteronism due to a concurrent benign cortical adenoma in the same adrenal gland with the ETT. 22,23 The pathologic features of adrenal ETT are very similar, to the point that they almost represent a distinct entity. In all cases, but one, the lesions were macrosopic cysts of a fair size, ≥3 cm in 8 of the 10 cases (Table 1), containing colloid-like material.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the ectopic thyroid tissue may have arisen because of abnormal migration or the heterotopic differentiation of uncommitted endodermal cells, but it is not possible to arrive at a definite cause, especially as there have been no similar cases reported. Immunohistochemistry, in situ hybridization, or other molecular studies might provide clues to the histogenesis of ectopic thyroid tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic thyroid tissue is commonly found in the head and neck along the thyroglossal duct; it does not differ microscopically from tissue observed in the thyroid gland. Ectopic thyroid tissue has also been detected in the lungs, gallbladder, small intestinal mesentery, pancreas, and adrenal gland . However, the development of ectopic thyroid tissue in the retroperitoneum below the diaphragm is extremely rare.…”
Section: Introductionmentioning
confidence: 99%
“…The thyroid gland tissue is composed of two cell types, the C cells and the thyroid follicular cells [28]. Romero-Rojas et al [2] showed that the lack of C cells in histology and immunohistochemical pro les is one of the important diagnostic criteria.…”
Section: Other Sitesmentioning
confidence: 99%